SAVORING LOYALTY: HOW BRAND GESTALT MEDIATES THE SOCIAL MEDIA-BRAND LOYALTY RELATIONSHIP - Lauren J. Lintang; David A. Lumangkun; Deske W. Mandagi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to construct and validate a theoretical framework that explains the impact of social media on café branding and customer loyalty, with brand gestalt serving as a mediating variable. The study employed a quantitative descriptive and correlational research design, collecting data through questionnaires from a sample of 200 Gen Z café customers in Manado City. Participants were recruited using a combination of snowball and convenience sampling techniques. Data analysis was performed using Structural Equation Modeling (SEM) to explore relationships within the dataset. The results show that SMM significantly impacts the story, servicescape, sensescape, stakeholder, and brand loyalty. Additionally, story, sensescape, and servicescape all significantly influence brand loyalty. Furthermore, Results indicate that the story dimension of brand gestalt mediates the relationship between SMM and brand loyalty. The emphasis on social media marketing may not fully capture the influence of other marketing channels, and the sample size or geographic scope might limit the generalizability of the results. Future research could explore emotional engagement, brand equity, or other digital marketing strategies like influencer and content marketing while expanding to different industries or regions for broader insights. The study contributes to the theoretical understanding of brand gestalt by highlighting how specific dimensions—story, sensescape, and servicescape—positively impact customer loyalty. It extends existing theories by demonstrating that these dimensions, along with social media marketing, play crucial roles in shaping brand perceptions and loyalty.